Preparation and evaluation of herbal cream - Dubey, Aditi; Prasad, Pushpa; Roy, Amit (Journal of Applied Pharmaceutical Research, 2014)
A herbal fairness cream was formulated using herbal extracts which have potential antioxidant activity. Creams were basically formulated using the hydro alcoholic extracts of Glycyrrhiza glabra (root and Stolons),Camellia sinensis (leaf), Pleurotus osttreatus (mushroom plant). The prepared formulation were subjected to different evaluation like spreadability, pH, appearance, viscosity, drug content, irritability and antioxidant properties. The prepared formulation was found stable and effective. Among the several combination Liquorice & Green Tea based preparation shows better results. From the results it was concluded that it is possible to develop creams containing herbal extracts having potent antioxidant and fairness property and can be used as the provision of a barrier to protect skin.